2014
DOI: 10.1117/1.jbo.19.10.108003
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial low-level laser therapy enhances learning, memory, and neuroprogenitor cells after traumatic brain injury in mice

Abstract: Abstract. The use of transcranial low-level laser (light) therapy (tLLLT) to treat stroke and traumatic brain injury (TBI) is attracting increasing attention. We previously showed that LLLT using an 810-nm laser 4 h after controlled cortical impact (CCI)-TBI in mice could significantly improve the neurological severity score, decrease lesion volume, and reduce Fluoro-Jade staining for degenerating neurons. We obtained some evidence for neurogenesis in the region of the lesion. We now tested the hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 48 publications
2
99
0
2
Order By: Relevance
“…Xuan et al hypothesized that tLLLT could improve performance on the MWM for learning and memory and increase neurogenesis in the hippocampus and subventricular zone (SVZ) after CCI TBI in mice. 67 TBI was created by subjecting the mice to a single right lateral CCI using a pneumatic impact device with 3 mm flat-tip rod at a speed of 4.8 m/sec with an impact depth of 2 mm. TBI mice were given one of two treatments: one laser treatment 4 h post-TBI or three daily applications (once per day).…”
Section: Tlllt Increases Neuroprogenitor Cellsmentioning
confidence: 99%
“…Xuan et al hypothesized that tLLLT could improve performance on the MWM for learning and memory and increase neurogenesis in the hippocampus and subventricular zone (SVZ) after CCI TBI in mice. 67 TBI was created by subjecting the mice to a single right lateral CCI using a pneumatic impact device with 3 mm flat-tip rod at a speed of 4.8 m/sec with an impact depth of 2 mm. TBI mice were given one of two treatments: one laser treatment 4 h post-TBI or three daily applications (once per day).…”
Section: Tlllt Increases Neuroprogenitor Cellsmentioning
confidence: 99%
“…Nevertheless, we were able to successfully demonstrate a significant enhancement of the neurogenic potential of RA (released from LR-NP) when combined with laser light in vivo. Recent data using low-level laser therapy revealed that near-infrared light (NIR) is capable of improving neurological performance in both patients and animal models of traumatic brain injury [41][42][43]. Interestingly, 18 J/cm 2 of NIR, the same fluence we used in our study, was able to increase the number of new neurons in the SVZ of mice with traumatic brain injury [43].…”
Section: Discussionmentioning
confidence: 53%
“…Recent data using low-level laser therapy revealed that near-infrared light (NIR) is capable of improving neurological performance in both patients and animal models of traumatic brain injury [41][42][43]. Interestingly, 18 J/cm 2 of NIR, the same fluence we used in our study, was able to increase the number of new neurons in the SVZ of mice with traumatic brain injury [43]. Since NIR has high clinical relevance, as it covers the tissue transparency window of the spectrum while sharing similar biological effects with blue light, namely on the induction of neurogenesis and mitochondria-derived ROS, it would be possible to bypass the invasive implantation of fiber-optic required for blue light treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial LLLT improved neuromuscular performance, increased brain derived neurotrophic factor (BDNF), reduced brain lesion volume, enhanced learning and memory, and overall improved the neurological severity score in mouse model of TBI [24,25,[28][29][30][31][32]. In addition, the clinical studies found that LLLT could improve cognition and decrease depression, anxiety, headache and insomnia in patients with chronic Review Xiang-Ping Chu and long-term spatial and recognition memory impairments in rats that were injected bilaterally with AÎČ 1-42 to the hippocampus CA1 region [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have shifted the focus of research to the application of LLLT on brain disorders [1][2][3]. During the past decade, LLLT has been widely used to study neurological and psychological diseases [3] such as depressionlike behaviors [4][5][6][7][8], Alzheimer's disease (AD) [9][10][11][12][13][14][15][16][17][18][19][20], Parkinson's disease [21], stroke [22,23] and traumatic brain injury (TBI) [24][25][26][27][28][29][30][31][32]. Because red or NIR light can effectively penetrate into brain tissues [33,34], it can be noninvasive and play a beneficial role in increasing ATP biosynthesis and neurogenesis [1,2].…”
Section: Introductionmentioning
confidence: 99%